Undiagnosed Diabetes Mellitus in Acute Coronary Syndrome (ACS) Patients - Awais Hussain Kazim, Muhammad Shahzad, Saima Rasheed, Ahmad Bilal, Noman Sadiq, Tahira Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Diabetes mellitus is a significant precursor of CAD. Patients hospitalised for suspected myocardial infarction had type 2 diabetes at higher rates than the general population, increasing the likelihood of cardiovascular complications. Hospitalized individuals with CAD have a worse prognosis if they also have diabetes mellitus. Objective: With this study, we want to quantify the prevalence of unrecognised diabetes mellitus among Acute Coronary Syndrome patients at a tertiary care hospital in Lahore. Study design: Cross sectional study Setting: Department of Cardiology, Bahria Town Hospital, Lahore Duration: Six months (09-2018 to 03-2019) Data collection procedure: One hundred forty patients who fulfilled the study's inclusion and exclusion criteria were included. Using a standardised questionnaire, we were able to collect information such as age, gender, and type of ACS (STEMI, Non-STEMI, or unstable angina). Diabetes was diagnosed by measuring fasting blood sugar and haemoglobin A1c in a serum sample of 3 cc. It was noted that untreated diabetes mellitus was present. Results: There were 110(78.6%) males and 30(21.4%) females in our study. The mean age of patients was 57.08±12.72 years. The mean height was 171.95±14.37 cm, mean weight was 80.70±11.23 kg and mean BMI was 26.89±3.64. There were 63(45%) patients with family history of diabetes. There were 60(42.9%) patients with Non-STEMI, 52(37.1%) with STEMI and 28(20%) with unstable angina. The mean HbA1c of the patients was 6.11±0.86. There were 10(7.1%) patients with undiagnosed Diabetes mellitus. Conclusion: 7 percent of ACS patients have diabetes mellitus that has not been diagnosed. Keywords: Undiagnosed Diabetes Mellitus, Acute Coronary Syndrome, type 2 diabetes, family history, STEMI,